Glacial Meltwater Identification in the Amundsen Sea - Biddle, Louise C.; Heywood, Karen J.; Kaiser, Jan; Jenkins, Adrian (Journal of Physical Oceanography, 2017)
Pine Island Ice Shelf, in the Amundsen Sea, is losing mass because of warm ocean waters melting the ice from below. Tracing meltwater pathways from ice shelves is important for identifying the regions most affected by the increased input of this water type. Here, optimum multiparameter analysis is used to deduce glacial meltwater fractions from water mass characteristics (temperature, salinity, and dissolved oxygen concentrations), collected during a ship-based campaign in the eastern Amundsen Sea in February-March 2014. Using a one-dimensional ocean model, processes such as variability in the characteristics of the source water masses on shelf and biological productivity/respiration are shown to affect the calculated apparent meltwater fractions. These processes can result in a false meltwater signature, creating misleading apparent glacial meltwater pathways. An alternative glacial meltwater calculation is suggested, using a pseudo-Circumpolar Deep Water endpoint and using an artificial increase in uncertainty of the dissolved oxygen measurements. The pseudo-Circumpolar Deep Water characteristics are affected by the under ice shelf bathymetry. The glacial meltwater fractions reveal a pathway for 2014 meltwater leading to the west of Pine Island Ice Shelf, along the coastline.